An integrated flare minimization methodology for simultaneous turnaround operations of two chemical plants. (20th December 2020) - Xu, Yiling; Wang, Sujing; Xu, Qiang
Abstract: Current flare minimization studies were exclusively focusing on single facility/plant under normal or abnormal operating conditions. Systematic studies are still lacking for simultaneous flare minimizations of multiple plants, which are all under their turnaround operations. In this paper, a novel methodology has been developed for simultaneous flare minimizations of two olefin plants under their turnarounds: one is to start up and the other is to shut down. Based on plant-wide dynamic modeling and simulation, new flare minimization opportunities coupling both start-up and shutdown operations have been explored and examined. Eventually, an integrated duo-plant flare minimization strategy has been identified and virtually demonstrated. A key merit of this study is that through the interplant material exchange, flaring sources from Plant A could be utilized by Plant B instead of being flared; meanwhile, flaring sources from Plant B could also be significantly reduced. Thus, the integrated flare minimization strategy has created a win-win situation that can simultaneously reduce flare emissions from both plants to their extreme potentials. Compared with conventional turnaround strategies, the case study performed in this paper shows that the total flaring amount for both olefin plants can be significantly reduced by 69.47%. Compared with a previous study, the flaring amount of the single plant has also been reduced by an extra of 18.18%. The development suggests potentially significant economic, environmental, and societal benefits. It has also laid a solid foundation for future studies and applications on simultaneous multi-plant flare minimizations through optimal design and scheduling of multi-plant interplant material exchanges. Graphical abstract: Image 1